Quality of attachment to father and mother and number of reciprocal friends - Veríssimo, Manuela (2011)
Attachment research suggests that children with secure attachments are more able to construct meaningful relationships with peers. Few studies, however, have attempted to map early attachment security to the formation and maintenance of preschool friendships. Special attention has been paid to affiliative relationships (particularly friendships) because these are presumed to be of special importance with respect to a number of developmental outcomes and social adjustment indices. This study examined the relations between mother–child and father–child attachment relationships using the attachment Q-sort (AQS) and the number of reciprocated friendships of preschool children. Thirty-five mother–child and father–child dyads from bi-parental families participated in the study. Children were between 29 and 38 months of age for the first assessment. The organisation of children’s secure base behaviour with both parents was assessed from separate observations of the child and parent at home. Subsequently, sociometric measures were used at four years of age to determine peer preferences. The correlation between the independent AQS scores for fathers and mothers was positive and significant (r = .51, p < .05). Thus, there was consistency in child secure base behaviour across visits with each parent. Bivariate correlation and regression analyses showed a significant positive relation between AQS security with fathers (but not with mothers) and the number of reciprocated friendships (r = .43, p < .05). Regression analyses indicated that AQS security with fathers remained a significant predictor of friendships even when AQS security with mothers was controlled. These findings may indicate a distinct relational effect of interaction quality with the father.